Mapping Global Information Design Research in Digital Interfaces: A Bibliometric Perspective on SDGs 4 and 9 - Hasanuddin Al Habib; Dimas Avian Maulana; Shofian Fiangga (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: To map the global development of research on information design in digital interfaces through the perspective of user interface (UI), user experience (UX), and usability studies. This study also examines its relevance to Sustainable Development Goal 4 (Quality Education) and Sustainable Development Goal 9 (Industry, Innovation and Infrastructure). Method: Bibliometric analysis was conducted using Scopus-indexed journal articles published between 2000 and 2026. Data were retrieved using the query TITLE-ABS-KEY (“UI” AND “UX” AND (“user experience” OR usability)). Following PRISMA-guided screening, 51 articles were selected for analysis. Performance analysis and science mapping using VOSviewer were applied to identify publication trends, source contributions, and thematic structures. Results: The findings indicate rapid growth of UI/UX research during the 2020s, with major contributions from computer science, engineering, and interdisciplinary fields. Thematic mapping shows that user experience, usability, and user interface represent the central research clusters, while design thinking and usability testing emerge as important supporting themes. Novelty: The study highlights information design as a strategic component in sustainable digital development. Effective interface structures support SDG 4 by improving accessibility and comprehension in digital learning environments, while supporting SDG 9 through the development of inclusive and human-centered digital infrastructure. The findings provide directions for future research on accessibility, usability evaluation, and sustainable interface design.